As classes sociais e o empresariamento na produção da linha 4-amarela do metrô de São Paulo (Brasil) - Scarcelli, Oliver Cauã Cauê França [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The July 2013 protests in Brazil, born out of the demand for revocation of the public transportation fare rise, exposed how challenging and distressing mobility had become in major Brazilian urban areas. Noteworthy is the situation of São Paulo - the neural center of Brazil's economy - given the enormous challenges its horizontal extension impose on urban mobility. Based on the heightened relevance urban public transportation policy discussions have gained in São Paulo, we explore the socio-spatial formation process of its subway lines, seeking to comprehend the transformations in its drawing and their respective roles in the planning and modelling of the urban space. In this article, we analyse the long creation process of subway Line 4 based upon its projects. Connecting five lines (including existing and planned ones) and three train commuter lines managed by São Paulo's Metropolitan Train Company (CPTM), this line is responsible for consolidation of a subway network in the metropolis, connecting the Old Downtown to the financial hotspots of Avenida Paulista and Berrini. We discuss the variations in its itinerary drawing from the 1968 planning sketches of the German- Brazilian Hochtief-Montreal-Deconsult until its most recent iteration implemented by the association of construction companies. We present these different projects in order to unveil the intentionalities informing each one of them. We conclude by arguing that neoliberalism caused a drastic reduction in the rhythm of the subway network expansion and that negotiations between São Paulo's Subway Company (Metrô) and investors defined the itinerary drawing of subway Line 4

As jornadas de junho de 2013, ciclo de protestos no Brasil que nasceu ligado à pauta pela revogação do aumento das tarifas do transporte coletivo, escancararam o penoso deslocamento nas grandes cidades brasileiras. Chama a atenção a situação da metrópole paulista - centro da economia brasileira -, devido à extensão de seu crescimento urbano horizontal, que impõe enormes desafios à mobilidade. Assim, dada a relevância que as discussões sobre transporte coletivo urbano assumem na metrópole, dedicamo-nos a pesquisar a formação socioespacial de suas linhas de metrô, a fim de compreender as transformações em seus traçados e seu papel na modelação do espaço urbano. Em nosso artigo, propomo-nos a analisar o longo processo de criação da Linha 4-Amarela do Metrô de São Paulo a partir de seus projetos. Integrando cinco linhas do Metrô (existentes e em implantação) e três linhas da Companhia Paulista de Trens Metropolitanos, essa Linha é responsável pela formação de uma rede de metrô na região metropolitana, conectando o centro velho da capital à Avenida Paulista e ao centro Berrini. Discutiremos as variações em seu traçados, desde os estudos de 1968 realizados pelo consórcio teuto-brasileiro Hochtief- Montreal-Deconsult até o plano executivo mais recente, levado a cabo pelos consórcios construtores. Apresentaremos as transformações nos projetos, procurando desvendar as intencionalidades por trás de cada um deles - e aqui verificamos que o neoliberalismo representou uma enorme inflexão no ritmo de expansão da rede e que negociações entre o Metrô e investidores (em Hong Kong, por exemplo) ditaram o traçado da Linha 4-Amarela
Keywords: Geografia urbana; Classes sociais; Estações do metrô; Transportes coletivos; Transporte urbano; Crescimento urbano; Espaço urbano; Planejamento urbano; Urbanização; São Paulo (SP)